Corporate competitiveness and communication practice in communication technologies – international comparison - Huszárik, Erika Seres; Kosár, Silvia Tóbiás; Korcsmáros, Enikő; Gódány, Zsuzsanna; Csinger, Bence (Publishing House of Wroclaw University of Economics and Business, 2023)
The technological changes of the Industry 4.0 period and the spread of communication and information technologies allow for a more efficient diversification of products and services in response to changing consumer needs. Modern ICT tools are used by all companies to varying degrees. The main aim of the primary research on which this study is based was to assess the challenges of small and medium-sized enterprises operating in Slovakia and Hungary, the factors influencing their competitiveness, and from this to learn which are the most effective communication technologies in Industry 4.0. The primary research was carried out in the form of a questionnaire survey, and the number of items of the examined international sample was 275 (145 SMEs in Hungary and 130 in Slovakia). In addition to the descriptive statistical analyses, the research questions and the related hypotheses were tested by ANOVA table and cluster analysis. The respondents from the two countries also have a unified view of the factors that help increase competitiveness. In connection with the cluster analysis, it can be stated that the business activity does not fundamentally affect whether the individual companies belong to the group of environmentally conscious people who rely on human resources and digitalisation, or to the group with negative attitudes who do not trust it. Companies still consider the constantly updated corporate website to be the most effective means of corporate communication, and although communication on social media is becoming more and more valuable, the respondents believe that the shift in communication through the website which would have been replaced by communication via the social network has not yet taken place.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 5-31
Keywords: competitiveness; communication technologies; company; IT tools